Seminoma and dysgerminoma: evidence for alignment of clinical trials and de-escalation of systemic chemotherapy - Wood, Georgina E.; Bunting, Christopher P.; Veli, Mesel; Arora, Rupali; Berney, Daniel M.; Alifrangis, Constantine; MacDonald, Nicola D.; Miller, Rowan E.; Shamash, Jonathan; Stoneham, Sara; Lockley, Michelle (Frontiers in Oncology, 2023)
Malignant germ cell tumours are a group of rare cancers whose incidence peaks in late adolescence and early adulthood. Dysgerminomas of the ovary and seminomas of the testis are analogous diseases, but seminomas have a 10-fold higher incidence. The two tumours are morphologically identical and are only differentiated by surrounding organ-specific tissue or testicular germ cell neoplasia in situ. They share genetic features including KIT and RAS mutations, amplification of chromosome 12p, and expression of pluripotency markers (NANOG (Nanog homeobox), OCT3/4 (Octamer-binding transcription factor 3/4), and SAL4 (Spalt-like trascription factor 4)). Both histologies are exquisitely sensitive to platinum chemotherapy, and the combination of bleomycin, etoposide, and cisplatin (BEP) yields survival rates greater than 90%. However, BEP causes significant, lifelong toxicity (cardiovascular, renal, respiratory, and neurological) in these young patients with an expectation of cure. Here, we comprehensively review the biological features of dysgerminoma and seminoma to demonstrate that they are biologically analogous diseases. We present available clinical trial data supporting de-escalation of chemotherapy treatment. Finally, we propose that future trials should enrol men, women, and children to benefit all patients regardless of age or sex.